Application of Assemblr Edu Augmented Reality Media in IPAS Learning on Water Cycle Material at Wonosari 01 State Elementary School - Amelia, Vera; Isdaryanti, Barokah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
IPAS can foster students' curiosity about their surroundings. It is very important to be taught in elementary school. However, based on the results of observations at Wonosari 01 State Elementary School, researchers obtained data that there was still a lack of student interest in IPAS subjects, because during learning the teacher did not use learning media so that students became less active in participating in learning. This also has an impact on student learning outcomes which are still relatively low. Researchers collaborate with classroom teachers in improving learning activities in the classroom. Researchers and class teachers use Augmented Reality Assemblr Edu learning media in IPAS subjects with water cycle material. This research uses the Classroom Action Research (PTK) method proposed by Kemmis and Taggar. This Classroom Action research method was conducted in two cycles. The results of this study indicate that there is an increase in the average student learning outcomes, where in each cycle student learning has increased from 83.46% in cycle I and 92.69% in cycle II. This is also shown in the percentage of completeness of student learning outcomes which is increasing from cycle I with a percentage of completeness of 84.61% and a percentage of 15.38% unsuccessful. While in cycle II the percentage of completeness was 96.15% with a percentage of unfinishedness of 3.84%. Based on the data obtained, the researcher's goal of applying Augmented Reality Assemblr Edu learning media can improve student learning outcomes in IPAS subjects has been proven successful.